A STUDY OF GLOBAL INDICATORS FOR THE WORLD ENERGY MARKET - I. Rykova; D. Taburov (Вестник Северо-Кавказского федерального университета)
This article is on the study of basic approaches to assess the contribution of the electric power sector to the growth of the world economy. The efficiencies of the global energy consumptions were studied: energy complex infrastructure improvement, the productivity growth of efficiency of technological equipment, the profitability of energy supplies business. The retrospective analysis defines the conditions of the declining intensity of primary energy in such countries as Azerbaijan, Bosnia and Hercegovina, Armenia. The article emphasis the depletion of energy, that's scrupulous leads to the principles of a "green" economy, whose propose to minimise carbon emission. This revealed an objective need for developing special power grids control mechanisms. The study identiies decisions for energy eficiency growth and capabilities of the country, required to the sound energy production in the context of globalisation.